Síntese de zeólitas e avaliação do uso como aditivo de misturas asfálticas mornas (MAM) - Amoni, Bruno de Castro (2014)
The zeolite phases NaP1 and Analcime, were successfully obtained by the reaction whith hydrothermal synthesis. The ash (C) and zeolite (CZ) were characterized by the techniques of: x-ray diffraction (XRD), infrared spectroscopy (FTIR), x-ray fluorescence (XRF), scanning electron microscopy (SEM), thermo gravimetric analysis (TGA). The x-ray technique allowed the identification of zeolitic phases, that were identified as NAP1 and analcime. Infrared spectroscopy showed the vibrations of TO4 tetrahedra of zeolite, as well as the vibration of the OH bond of the water molecule. The morphology of the crystals was evidenced by the technique of scanning electron microscopy, where it was observed that the zeolite crystals NAP1 were masked by impurities, which prevented the refinement of the phases. The thermal stability of the crystals was established by thermo gravimetric analysis, where the CZ sample showed higher weight loss compared to sample C. This mass comes from the water present in the pores of the zeolite, which makes it suitable for the preparation of warm asphalt mixtures (WAM). Samples C and CZ have been used as additives for asphalt binder (AB), where they were effective in increasing resistance to deformation. The modified asphalt binder samples were characterized by the techniques of: penetration (PEN), softening point (SP), Brookfield viscosity and rheological analysis using a dynamic shear rheometer (DSR). Samples of modified AB showed no significant differences in the values of penetration and softening point. The viscosity of the samples with modified AB were higher than that of orinal AB. The rheologies of modified AB showed favorable results of G * and , where the modified LA showed greater resistance to deformation. the values of performance grade (PG) showed no changes compared to original AB.